Peran Politik Hukum Dalam Polemik Hukuman Mati Pelaku Tindak Pidana Korupsi - Afifi, Miftach Rizcha; Uswatun C, Melyssa; Lazuardi , Alya Salsabilla (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
The reform era was welcomed by the people of Indonesia, marking the collapse of the New Order government regime, which was considered very detrimental to the country due to corruption. However, the culture of corruption has not completely disappeared and even the efforts to combat corruption in Indonesia have not shown brilliant achievements. The weak implementation of the law for corruption convicts despite being regulated in the corruption law has made this practice spread from the village level to the center or state. Law enforcers who are supposed to be the spearhead of eradicating corruption are actually involved in corrupt practices. So that this corruption phenomenon needs to be studied and researched further in the role of legal politics as an evaluation of efforts to eradicate corruption in Indonesia.